Thermochemistry of N-Heterocyclic Carbenes with 5-, 4-, 3-, and 2-Membered Rings - BLEDA, ERDİ ATA; ALTUN, ZİKRİ (WILEY, 2014)
N-heterocyclic carbenes (NHCs) based on imidazole-2-ylidene (1) or the saturated imidazolidine-2-ylidene (2) scaffolds are long-lived singlet carbenes. Both benefit from inductive stabilization of the sigma lone pair on carbon by neighboring N atoms and delocalization of the N pi lone pairs into the nominally vacant p-pi atomic orbital at the carbene carbon. With thermochemical schemes G4 and CBS-QB3, we estimate the relative thermodynamic stabilization of smaller ring carbenes and acyclic species which may share the keys to NHC stability. These include four-membered ring systems incorporating the carbene center, two trivalent N centers, and either a boron or a phosphorus atom to complete the ring. Amino-substituted cyclopropenylidenes have been reported but three-membered rings containing the carbene center and two N atoms are not known. Our calculations suggest that amino-substituted cyclopropenylidenes are comparable in stability to the four-membered NHCs but that diazacyclopropanylidenes would be substantially less effectively stabilized. Concluding the series are acyclic carbenes with and without neighboring N atoms and a series of two-membered ring azapropadienenylidene cations of form :CNW with W = an electron-withdrawing agent. We have studied W = NO2, CH2(+), CF2(+), and (CN)(2)C(+). Although these systems display a degree of stabilization and carbene-like electronic structure, the stability of the NHCs is unsurpassed. (c) 2014 Wiley Periodicals, Inc.
Keywords: N-heterocyclic carbenes; acyclic carbenes; amino-substituted cyclopropenylidenes; thermodynamic stability; carbene singlet; triplet gaps; ELECTRONIC-STRUCTURE; HEAT; SPECTROSCOPY; STABILITY